Women’s language analysis used by female characters in mulan movie - Anggreani, Sarah; Anggraeni, Diana; Wulansari, Dini (Trigin Institute, 2024)
Women’s language and its features have been a subject of linguistic study for decades. This research explores the women's language features used by female characters in the 2020 movie